2020
DOI: 10.1021/acsami.0c14246
|View full text |Cite
|
Sign up to set email alerts
|

Graphene Quantum Dot-Sensitized ZnO-Nanorod/GaN-Nanotower Heterostructure-Based High-Performance UV Photodetectors

Abstract: The fabrication of a superior-performance ultraviolet (UV) photodetector utilizing graphene quantum dots (GQDs) as a sensitization agent on a ZnO-nanorod/GaN-nanotower heterostructure has been realized. GQD sensitization displays substantial impact on the electrical as well as the optical performance of a heterojunction UV photodetector. The GQD sensitization stimulates charge carriers in both ZnO and GaN and allows energy band alignment, which is realized by a spontaneous time-correlated transient response. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
57
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 84 publications
(59 citation statements)
references
References 59 publications
1
57
1
Order By: Relevance
“…The FWHM values of omega scan along (0002) and (10–12) were found to be 0.39° and 0.84° attributing to screw dislocation density of ~ 1.91 × 10 9 cm −2 and edge dislocation density of ~ 2.33 × 10 10 cm −2 , respectively. These dislocation densities are found to be lower in comparison to the previously reported GaN NTs structure grown on Si (111) substrate with thicker AlN buffer layer (665 nm) at a lower growth temperature (762 °C) 16 .
Figure 2 ( a ) HRXRD omega scan along (0002) & (10–12) plane of diffraction, ( b ) Planar view FESEM image (inset: shows a single NT), ( c ) Cross-sectional FESEM image of GaN NTs.
…”
Section: Resultscontrasting
confidence: 73%
See 1 more Smart Citation
“…The FWHM values of omega scan along (0002) and (10–12) were found to be 0.39° and 0.84° attributing to screw dislocation density of ~ 1.91 × 10 9 cm −2 and edge dislocation density of ~ 2.33 × 10 10 cm −2 , respectively. These dislocation densities are found to be lower in comparison to the previously reported GaN NTs structure grown on Si (111) substrate with thicker AlN buffer layer (665 nm) at a lower growth temperature (762 °C) 16 .
Figure 2 ( a ) HRXRD omega scan along (0002) & (10–12) plane of diffraction, ( b ) Planar view FESEM image (inset: shows a single NT), ( c ) Cross-sectional FESEM image of GaN NTs.
…”
Section: Resultscontrasting
confidence: 73%
“…Therefore, growth of high surface-to-volume ratio and stress relaxed 3D GaN-NSs could play a crucial role in the development of highly efficient optoelectronic devices. Recently, it has been reported that GaN-nanocolumnar structure offers wavelength tunability, low dislocation density and lower lattice related strain along with very good response 14 16 . However, the fabricated devices are reported to be non-operational in photovoltaic mode i.e.…”
Section: Introductionmentioning
confidence: 99%
“…These dislocation densities are found to be lower in comparison to the GaN NTs structure grown on Si (111) substrate with thicker AlN buffer layer (665 nm) at lower growth temperature (762 o C). [16] demonstrates a high magnification image of layer by layer growth of single GaN-NT. Figure 2(c) displayed the cross -sectional view of the novel hexagonal GaN-NTs having length of ~4.168 µm grown along the direction perpendicular to the substrate with AlN-buffer layer (~580nm) sandwiched between them.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, it has been reported that GaN-nanocolumnar structure can offers wavelength tunability, low dislocation density and lower lattice related strain and very good response. [14][15][16] However, the fabricated devices are non-operational in photovoltaic mode i.e. zero applied bias and display very high response time.…”
Section: Introductionmentioning
confidence: 99%
“…This hole-trapping mechanism through oxygen adsorption and desorption in ZnO NRs augments the high density of trap states usually found in NRs due to the dangling bonds at the surface and thus enhances the NW photoresponse. 8,14,15 However, a high bias voltage must be applied in order to obtain a high responsivity, which results in a long response time. ZnO-based p-n photodiodes have the advantages of fast response times, no applied elds, and no oxygen dependency.…”
Section: Introductionmentioning
confidence: 99%